Perception of stress and work fatigue in workers of a maquiladora company in the state of Nuevo León, Mexico. - Macias Nuñez, Nora Isela; Ibarra González, Victor Hugo; Gutierrez Muñoz, Mayra Lucero; Calderon Parga, Martha Esthela; Peña Moreno, Jose Armando (International Journal of Scientific Research and Management (IJSRM), 2023)
Nowadays in the organizations there are different changes, such as the demands, the fulfillment of objectives or the new tendencies of processes, in this sense the workers are affected by these changes, which are manifested in symptomatology that in the same way affects the organization, in this study two psychosocial phenomena were taken into account, which are Stress and Work Fatigue. It was carried out under a non-experimental, expository and transversal design, in a maquiladora organization, with a representative sample of 190 male and female employees, of different levels of schooling and positions. The instruments used were: The Symptomatic Stress Scale (ESS) of Seppo-Aro (1980), and the Subjective Patterns of Fatigue Questionnaire (PSF), elaborated by H. Yosithake (1978). The results of the sample were broken down into three sections: gender, type of contract and hierarchical level. The general objective was to identify the prevalence of work stress and fatigue perceived by the human capital of this organization, and the specific objectives were to identify whether there is a difference in the prevalence of work stress and fatigue in terms of hierarchical levels, both operational and administrative, and a second specific objective was to identify the prevalence of work stress and fatigue in terms of gender, female and male within this organization.